Alternative Therapeutic Interventions: Antimicrobial Peptides and Small Molecules to Treat Microbial Keratitis - Jadi, Praveen Kumar; Sharma, Prerana; Bhogapurapu, Bharathi; Roy, Sanhita (Frontiers in Chemistry, 2021)
Microbial keratitis is a leading cause of blindness worldwide and results in unilateral vision loss in an estimated 2 million people per year. Bacteria and fungus are two main etiological agents that cause corneal ulcers. Although antibiotics and antifungals are commonly used to treat corneal infections, a clear trend with increasing resistance to these antimicrobials is emerging at rapid pace. Extensive research are carried out to determine alternative therapeutic interventions and antimicrobial peptides (AMPs) are increasingly recognised for their clinical potential in treating infections. Small molecules targeted against virulence factors of the pathogens and natural compounds are also explored to meet the challenges and growing demand for therapeutic agents. Here we review the potential of AMPs, small molecules and natural compounds as alternative therapeutic interventions for treatment of corneal infections to combat antimicrobial resistance. Additionally, we have also discussed about the different formats of drug delivery systems for optimal administration of drugs to treat microbial keratitis.